The Effect of Training on Motivation and Productivity of Micro, Small, and Medium Enterprises In The Regency of Kombut District - Yustina Warum; Djabir Hamzah; Sumardi Sumardi; Rusianti Amat Sugio (Magister Management, Hasanuddin University, 2020)
The study aims to know and analyze the impact of training on motivation, to know and to analyse the impact of training on productivity, to know and analyze the impact of motivation on productivity, to know and to analyze the impact of training on the productivity of micro, small and medium enterprises (MSMEs) in the district of Kombut of Boven Digoel District if mediated by motivation. Methodology Research uses a quantitative approach to using the analysis of the pathway (path). Population and samples amounted to 89 respondents with a total sampling of the sampling techniques where the number of samples was equal to the population. Data processing method using smart PLS 3. The results of the study showed 1) that the training variables were partially positive and significant to the motivation. 2) Variable training has been partially positive and significant to the business productivity, 3) The motivation variable positively and significantly affects the business productivity, 4) The training variables positively and significantly affect the productivity